1960
DOI: 10.2307/1539058
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Potassium Deficiency on the Free Amino Acid Pattern of the Muscle Tissue of Protein-Maintained Fundulus Heteroclitus ,

Abstract: In this investigation the effect of a low potassium environment on the free amino acid pattern of the skeletal muscle tissue of the killifish, Fundulus heteroclitus, has been studied in an attempt to determine if the changes observed in the potassium-deficient rat (Eckel, Pope and Norris, 1954;Iacobellis, Muntwyler and Dodgen, 1956) could also be found in other members of the vertebrate subphylum. Apparently the rat, but not the dog (Iacobellis, Griffen and Muntwyler, 1957), is capable of replacing part of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1964
1964
1966
1966

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The part played by organic substances in the blood of elasmobranchs in accommodation to different salinities was reviewed by Smith (1936) (and see 11.398); do similar adaptive changes in organic components of the blood occur in teleosts and cyclostomes? It is difficult to answer this question, partly because of the relative lack of data, but also because significant differences are found in different species or a single species at different stages in the life history (Fontaine & Ibanes, 1935;Kubo, 1954Kubo, , 1955Saito, 1954;Svard, 1958;Sano, 1960;Jones & Macleod, 1960;Cowey, Daisley & Parry, 1962), or when fed on different diets (Wood, Yasutake, Woodall & Halver, 1957a, b ;Hanlon, 1960). Not only are total quantities of nitrogen different (range 3-3-5'8 g./Ioo ml., Deutsch & McShan, 1949) but also the contributions of the components; for instance, carp and brook trout exhibit quite different albumen: globulin ratios (Field, Elvehjem & Juday, 1943).…”
Section: (B) the Composition Of Jish Bloodmentioning
confidence: 99%
“…The part played by organic substances in the blood of elasmobranchs in accommodation to different salinities was reviewed by Smith (1936) (and see 11.398); do similar adaptive changes in organic components of the blood occur in teleosts and cyclostomes? It is difficult to answer this question, partly because of the relative lack of data, but also because significant differences are found in different species or a single species at different stages in the life history (Fontaine & Ibanes, 1935;Kubo, 1954Kubo, , 1955Saito, 1954;Svard, 1958;Sano, 1960;Jones & Macleod, 1960;Cowey, Daisley & Parry, 1962), or when fed on different diets (Wood, Yasutake, Woodall & Halver, 1957a, b ;Hanlon, 1960). Not only are total quantities of nitrogen different (range 3-3-5'8 g./Ioo ml., Deutsch & McShan, 1949) but also the contributions of the components; for instance, carp and brook trout exhibit quite different albumen: globulin ratios (Field, Elvehjem & Juday, 1943).…”
Section: (B) the Composition Of Jish Bloodmentioning
confidence: 99%
“…As a result, a possible function of lysine and arginine may be to act as cations to balance the decreased potassium ion concentration in the cells. Based on his studies cm potassiumdefieient Fundulus heteroelitus, Hanlon (1960) suggested such a function for lysine.…”
mentioning
confidence: 99%